The Electronic and Optical Properties of an Exciton, Biexciton and Charged Excitons in CdSe/CdTe-Based Multi-Shell Type-II Quantum Dot Nanocrystals - Koc, Fatih; Sahin, Mehmet (Springer Heidelberg, 2019)
It has been recently reported that multi-shell type-II quantum dot nanocrystals (QDNCs) have higher quantum yields. Besides these higher quantum yields of multi-shell type-II QDNCs, additional second layer has been a critical influence on the formation mechanisms of the excitonic structures. Understanding of bound and unbound cases of the excitonic structures in multi-shell type-II QDNCs gives some important information for applications. In this study, we have investigated the electronic and optical properties of a single exciton (X), biexciton (XX), and positively and negatively charged excitons (X+ and X-) in CdSe/CdTe-based multi-shell type-II QDNCs. In the study, three different structure compositions, i.e., CdSe/ CdTe, CdSe/CdTe/CdS, and CdSe/CdTe/ZnTe, have been considered. We have observed that CdS and ZnTe materials have drastically changed the electronic and optical properties of the bare CdSe/CdTe type-II QDNCs.
Sahin, Mehmet/0000-0002-9419-1711; Koc, Fatih/0000-0002-4751-2340